2008
DOI: 10.1128/aem.02099-07
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Prevalence in the Genus Azospirillum and Analysis of the First Genome Sequence of an Azospirillum brasilense Integrative Phage

Abstract: The prevalence of bacteriophages was investigated in 24 strains of four species of plant growth-promoting rhizobacteria belonging to the genus Azospirillum. Upon induction by mitomycin C, the release of phage particles was observed in 11 strains from three species. Transmission electron microscopy revealed two distinct sizes of particles, depending on the identity of the Azospirillum species, typical of the Siphoviridae family. Pulsed-field gel electrophoresis and hybridization experiments carried out on phage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
4
13
0
5
Order By: Relevance
“…This region could correspond to the 65-kb prophage previously isolated from this strain [15]. This putative prophage of A. brasilense Sp245 shows no homology to a prophage sequence obtained from A. brasilense Cd, an observation which is consistent with the absence of hydridization signal previously reported [15]; in addition, this region has no equivalent in the genome of A. brasilense CBG497.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This region could correspond to the 65-kb prophage previously isolated from this strain [15]. This putative prophage of A. brasilense Sp245 shows no homology to a prophage sequence obtained from A. brasilense Cd, an observation which is consistent with the absence of hydridization signal previously reported [15]; in addition, this region has no equivalent in the genome of A. brasilense CBG497.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, very little synteny was found between replicons of Azospirillum strains and more genomic rearrangements could be pinpointed in Azospirillum genomes compared to rhizobial genomes known for their genome plasticity [12]. This extraordinary genome plasticity was previously described experimentally in Azospirillum : indeed, the appearance of phenotypic variants was correlated with plasmid loss or reorganization [14] and the presence of bacteriophages was evidenced [15]. …”
Section: Introductionmentioning
confidence: 99%
“…The latter may indicate the strengthening of the root system formation which is consistent with literature data on the stimulating effect of Azospirillum on wheat [23,24]. Some properties of bacteriophage FAb-Sp7 isolated from the A. brasilense Sp7 cells have been described earlier [18]. In our studies, the mean number of roots after the treatment of wheat seedlings with bacteriophage preparations was actually unchanged (Table 2).…”
Section: Introductionsupporting
confidence: 81%
“…In most cases, bacteriophages were isolated from various environmental objects, including soil [12][13][14][15][16][17], and just some studies describe bacteriophages from soil bacteria associations. Thus, in the study of 24 soil bacteriophage strains that stimulate the growth of plants, it was first found [18] Our purpose was to study the effect of Azospirillum bacteriophages on the growth and development of the root system in wheat seedlings in an in vitro microorganism-plant system.…”
Section: Introductionmentioning
confidence: 99%
“…GTA particles in R. capsulatus are known to contain an ϳ4.5-kb DNA fragment (29). A 10-kb DNA fragment associated with GTA has been reported in the alphaproteobacterium Azospirillum lipoferum (6). Recently it was found that virus-like particles released from Silicibacter sp.…”
Section: Ism Produces Inducible Virus-like Particles (Vlps)mentioning
confidence: 99%